2022
DOI: 10.1111/hiv.13245
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of and risk factors for liver damage in patients with HIV‐1 mono‐infection receiving antiretroviral therapy

Abstract: ObjectivesThe study aimed to investigate the incidence of and risk factors for liver damage in patients with human immunodeficiency virus type‐1 (HIV‐1) mono‐infection receiving antiretroviral therapy (ART).MethodsWe retrospectively analyzed the clinical data of patients who were diagnosed with HIV‐1 infection and initiated ART from January to December 2017. Among them, 382 patients with HIV‐1 mono‐infection and normal baseline liver function were included in the analysis. The incidence of liver damage at each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
2
1
0
Order By: Relevance
“…In this study, liver damage was observed in 20% (491/2440) of the participants, a prevalence in line with earlier studies that reported figures ranging from 12% to 27% [ 19 , 20 ]. However, it is noteworthy that the highest incidence of liver damage reported in this study was 48%, occurring within the initial 3 months following the commencement of cART.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, liver damage was observed in 20% (491/2440) of the participants, a prevalence in line with earlier studies that reported figures ranging from 12% to 27% [ 19 , 20 ]. However, it is noteworthy that the highest incidence of liver damage reported in this study was 48%, occurring within the initial 3 months following the commencement of cART.…”
Section: Discussionsupporting
confidence: 92%
“…However, it is noteworthy that the highest incidence of liver damage reported in this study was 48%, occurring within the initial 3 months following the commencement of cART. This rate is both higher and faster than what was observed in a previous study (35% at 9 months) [19]. Nearly half of the patients in this cohort were older adults, aligning with the prevalent demographic trend among patients in Guangxi province [21,22].…”
Section: Comparison With Previous Worksupporting
confidence: 75%
“…In the present study, a negative correlation was found between TBIL and immune recovery in PLWH. Some study [ 48 , 49 ] found higher HIV RNA and longer duration of HIV viremia were the independent factors to increased risk of HCC, and the presence of liver damage was substantially linked with HIV-1 viral load. While no prior investigation has explicitly illuminated this observation, our supposition is that abnormal liver function could potentially affect the metabolism and absorption of ART drugs, which may decrease treatment efficacy and affect disease progression.…”
Section: Discussionmentioning
confidence: 99%